Ethylenediaminetetraacetic Acid‑Dependent Pseudothrombocytopenia in Patient Previously Treated as Dengue Fever - Hendra Wana Nur’amin; Muhammad Darwin Prenggono; Wivina Riza Devi (Berkala Kedokteran, 2021)
Abstract: One of the most widely used anticoagulants for a complete blood count is ethylenediaminetetraacetic acid (EDTA).  Pseudothrombocytopenia (PTCP) may be caused by EDTA, this condition may lead to inappropriate diagnosis and treatment. We report a 25-year-old female with unspecific headache and joint pain with very low platelet count since 1 month before hospital admission. She was diagnosed with Dengue fever infection and got some platelet transfusion from the previous secondary hospital. She was carried out for a blood test with another anticoagulant (sodium citrate) and bone marrow aspiration. The results showed that she had normal platelet count and bone marrow cellularity. When a patient was identified with thrombocytopenia without any bleeding manifestation, hematology disease, and family history, PTCP should be taken into consideration to prevent unnecessary intervention. Keywords: platelet, pseudothrombocytopenia, ethylenediaminetetraacetic acid, Dengue fever